Clinicopathological characteristics and treatment outcomes of adult - Keskin, Serkan; Basaran, Mert; Kilicaslan, Isin; Tunc, Murat; Bavbek, Sevil (Canadian Urological Association Journal, 2013)
Introduction: We report our experience with 8 consecutive adults treated for paratesticular rhabdomyosarcoma (RMS) at a single institution between 2000 and 2010. Methods: After primary surgical excision, 7 patients were classified into group I according to the Intergroup Rhabdomyosarcoma Study Group (IRSG) Postsurgical Grouping Classification, and 1 patient into group IIB. Retroperitoneal node dissection was not a required staging procedure. Adjuvant chemotherapy was administered to 7 of the 8 patients. No additional radiotherapy was administered. Results: The median age at diagnosis was 24 years (range: 18-60). Embryonal histology was the most common (75%) subtype. During follow-up, 3 patients experienced local relapse and 5 distant relapse. The median progression-free and overall survival times were 17.0 ± 9.9 months (range: 5-31) and 27.3 ± 1.3 months (range: 16-58), respectively. Conclusion: Paratesticular RMS is an uncommon malignancy in adults. We confirm that patients with localized paratesticular RMS may have different prognoses. Retroperitoneal lymphadenectomy can be avoided as a treatment for paratesticular RMS after radical inguinal orchiectomy.